[PP.10.24] EFFECTS OF TNF-ALPHA INHIBITON ON HEMODYNAMIC PARAMETERS AND BIOMARKERS IN RESISTANT HYPERTENSION: BACKGROUND, RATIONALE, AND DESIGN. (September 2016) - De Faria, A.; Ritter, A.; Catharina, A. Santa; Brunelli, V.; Correa, N.; Sabbatini, A.; Almeida, A.; Barbaro, N.; Moreno, H.; Modolo, R.
Abstract : Objective: Currently it has been largely discussed the influence of inflammation in resistant hypertension (RH). The BP variation promotes increased expression of pro-inflammatory cytokines, such as tumor necrosis factor-alpha, interleukins 1 and 6. It was showed that treatment with TNF- α inhibitor improves BP and endothelial function, and reduces arterial stiffness in patients with rheumatoid arthritis. Recently, it was demonstrated that TNF- α levels are increased in RH subjects compared to normotensives. This project aims to assess whether the acute inhibition of TNF- α reduces BP levels, as well as changes hemodynamic parameters, target organ damage and inflammatory biomarkers in RH. Design and method: This crossover, double-blind study will include 12 resistant hypertensive subjects –regularly followed at the Outpatient Resistant Hypertension Clinic/UNICAMP – which will randomized assigned to (1) serum infusion followed by infliximab infusion (TNF- α inhibitor, 3 mg/kg) and (2) infliximab followed by serum, for two hours and washout of the 40-day period between both infusions. Office, central and ABPM BP, inflammatory biomarkers, cardiac hypertrophy (echocardiography), endothelial function by flow-mediated dilation, arterial stiffness by pulse wave velocity (Sphygmocor CPV system) will be determined before and after 7 days of infusion. Hemodynamic parameters will be simultaneously assessed during infusions. The plasma concentrations of TNF- α, ILs-1, -6 e -10, monocyte chemoattractant protein-1, and adiponectin will be determined by ELISA. Results: Since the inflammatory process is associated in pathophysiology of RH and the lack of BP control, and because the TNF- α is implicated in cardiovascular outcomes, we hypothesized that acute TNF- α inhibition reduces BP levels, as well as modulates hemodynamic parameters, target organ damage and biomarkers in RH subjects. Conclusions: As the effect of TNF- α inhibition has not been explored in RH, this study may offer news perspectives on disease pathogenesis and treatment, which could provide a more rational approach to subjects at high cardiovascular risk